INTEGRATING INDUSTRIAL–ORGANIZATIONAL PSYCHOLOGY AND HUMAN FACTORS TO ENHANCE HUMAN PERFORMANCE IN AVIATION - Psomas, Efstratios (E-Journal VFU, 2025)
This article explores the integration of Industrial–Organizational Psychology and Human Factors to enhance human performance, safety, and decision-making in aviation. The study draws upon empirical and theoretical foundations to analyze how cognitive, behavioral, and organizational processes affect pilot efficiency and flight safety. Using a mixed methodological approach that combines qualitative observation and quantitative data, the paper identifies critical determinants of human reliability, including fatigue, stress, workload management, and mental health. The analysis highlights the central role of psychological assessment, training systems, and leadership culture in fostering resilience and adaptive expertise among aviation professionals. Findings indicate that applying evidence-based psychological principles within aviation environments improves decision quality, reduces human error, and supports proactive safety management. The proposed integrated framework emphasizes the continuous interaction between individual capabilities and organizational systems, offering a scientific basis for optimizing performance, minimizing risk, and cultivating psychological well-being in high-reliability aviation contexts.
Keywords: Industrial–Organizational Psychology; Human Factors; Aviation Safety; Human Performance; Decision-Making